2004
DOI: 10.1534/genetics.104.029561
|View full text |Cite
|
Sign up to set email alerts
|

The Enhancer-Blocking Activity of the Fab-7 Boundary From the Drosophila Bithorax Complex Requires GAGA-Factor-Binding Sites

Abstract: In the work reported here we have analyzed the role of the GAGA factor [encoded by the Trithorax-like (Trl) gene] in the enhancer-blocking activity of Frontabdominal-7 (Fab-7), a domain boundary element from the Drosophila melanogaster bithorax complex (BX-C). One of the three nuclease hypersensitive sites in the Fab-7 boundary, HS1, contains multiple consensus-binding sequences for the GAGA factor, a protein known to be involved in the formation and/or maintenance of nucleosome-free regions of chromatin. GAGA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
105
1
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 102 publications
(112 citation statements)
references
References 71 publications
4
105
1
2
Order By: Relevance
“…S3a), confirming that GATA by itself is sufficient for the boundary activity. It should also be noted that the enhancer blocker activity is not a property of any repetitive element but rather is an attribute of GATA SSR exclusively, as earlier reports from our lab have shown that GAGAG repeat fails to act as a boundary despite GAGAG motif having the ability to recruit GAGA boundary factor 25 .…”
Section: Gata Ssr Functions As Enhancer Blocker In Human Cellsmentioning
confidence: 77%
“…S3a), confirming that GATA by itself is sufficient for the boundary activity. It should also be noted that the enhancer blocker activity is not a property of any repetitive element but rather is an attribute of GATA SSR exclusively, as earlier reports from our lab have shown that GAGAG repeat fails to act as a boundary despite GAGAG motif having the ability to recruit GAGA boundary factor 25 .…”
Section: Gata Ssr Functions As Enhancer Blocker In Human Cellsmentioning
confidence: 77%
“…Moreover, the GAGA-binding sites in HS1 are important for boundary function. In previous studies, we found that the enhancer blocking activity of the minimal 1.2 kb boundary is compromised in both the embryo and adult when GAGA sites 1-5 are mutated (Schweinsberg et al, 2004). Although this finding indicates that GAGA (or another protein that recognizes the GAGA consensus) is required for Fab-7 boundary activity throughout development, the GAGA sites are not functionally equivalent.…”
Section: Introductionmentioning
confidence: 77%
“…For example, such a role has been suggested for GAF in the case of Fab-7 and SF1 insulators, which have many GAF binding sites. 45,46 Thus, further studies are necessary for elucidating the role of BTB domains of the ttk group in longdistance interactions and their other possible activities in transcriptional regulation.…”
Section: Discussionmentioning
confidence: 99%